2018
DOI: 10.23960/aec.v3.i2.2018.p139-147
|View full text |Cite
|
Sign up to set email alerts
|

Review: Fitoremidiasi Limbah Logam Berat dengan Tumbuhan Akar Wangi (Vetiveria zizanioides L)

Abstract: Fitoremediasi adalah teknologi pembersihan, penghilangan atau pengurangan polutan berbahaya, seperti logam berat, pestisida, dan senyawa organik beracun dalam tanah atau air dengan menggunakan bantuan tanaman (hiperaccumulator plant). Tanaman akar wangi atau vetiver merupakan tanaman dari famili Gramineae (rumput-rumputan) yang masih satu famili dengan serai wangi (citronella) dan serai dapur (lemon grass). Kelebihan tanaman ini adalah kemampuannya untuk menyerap bahan bahan racun berbahaya (B3) dan logam bera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
4
0
4
Order By: Relevance
“…This may also cause the concentration of Cr in the soil at 300 ppm treatment and the concentration of Ni in the soil at 150 ppm and 300 ppm treatments to increase after 28 days of exposure to heavy metal wastewater. This statement is also supported by the research conducted by Patandungan et al and Ambarwati and Bahri [1,23] who stated that C. zizanioides demonstrate great potential in processing heavy metal wastewater so that further research is needed. Research by Danh et al [6] also showed that vetiver was able to accumulate heavy metals in higher amounts than other plants.…”
Section: Phytoremediation Potential Of Vetiver (C Zizanioides)mentioning
confidence: 66%
“…This may also cause the concentration of Cr in the soil at 300 ppm treatment and the concentration of Ni in the soil at 150 ppm and 300 ppm treatments to increase after 28 days of exposure to heavy metal wastewater. This statement is also supported by the research conducted by Patandungan et al and Ambarwati and Bahri [1,23] who stated that C. zizanioides demonstrate great potential in processing heavy metal wastewater so that further research is needed. Research by Danh et al [6] also showed that vetiver was able to accumulate heavy metals in higher amounts than other plants.…”
Section: Phytoremediation Potential Of Vetiver (C Zizanioides)mentioning
confidence: 66%
“…Tumbuhan Vetiver zizanoides ditunjukkan pada Gambar 3 [22]. Tumbuhan ini memiliki karakteristik batang tegak dan kaku sehingga sangat kuat dalam menahan aliran air yang cukup deras [23]. Vetiver memiliki penyisihan kadar tembaga 95,56 % [24].…”
Section: Vetiver Zizanoidesunclassified
“…Tumbuhan ini dapat bertahan pada kondisi tanah dan iklim ekstrim serta tanah pegunungan yang mengalami erosi serta cocok dalam menahan aliran air (scouring of water flow) [25]. Pemilihan tumbuhan sebagai fitostabilitator karena Vetiveria zizanoides merupakan salah satu tumbuhan lokal yang cepat beradaptasi di lingkungan pencemar logam berat [23], menghasilkan biomassa yang [23], tumbuh lebih baik di aliran sungai [25], akar tumbuhan Vetiveria zizanoides dapat bertahan pada tanah yang terkontaminasi tembaga yaitu pada konsentrasi 1762 mg/kg [26].…”
Section: Vetiver Zizanoidesunclassified
“…Not all types of plants can be used as road shade plants, as road shade plants there are certain conditions that must be met [6] said the characteristics of good shade trees planted include: (1) better absorption of CO2 and lead gases; (2) can produce Oxygen; (3) tree height is more than two meters but not more than 12 meters; (4) lush with leaf density that can cover the sun's rays; (5) broad canopy or able to cover a large area; (6) maintenance is easy; (7) the branches are not easily broken when blown by strong winds; (8) twigs or branches are not too large, because it is dangerous if they fall and fall on people who are under them; (9) strong roots into the ground so that trees do not fall easily when blown by strong winds, roots do not come out to the surface which can damage floors and walls of houses or sidewalks.…”
Section: A Introductionmentioning
confidence: 99%
“…The mechanism of phytoremediation can be in the form of active absorption (rhizofitration) and passive absorption. Research on various kinds of plants has been carried out to determine the potential of each of these plants in absorbing air pollution [9]. Conservation education carried out for children and adolescents plays an important role in shaping the character of the community in the future.…”
Section: A Introductionmentioning
confidence: 99%